The impact of supervision on bank performance - Beverly J. Hirtle; Anna Kovner; Matthew Plosser (Federal Reserve Bank of New York, 2016)
Does the intensity of supervision affect quantifiable outcomes at supervised firms? We develop a novel proxy to identify plausibly exogenous variation in the intensity of supervision across large U.S. bank holding companies (BHCs), based on the size rank of a BHC within its Federal Reserve district. We begin by demonstrating that the largest five BHCs in a district receive discontinuously more supervisory time than smaller BHCs in the district, even after controlling for size and a variety of other BHC characteristics. Using a matched sample approach, we find that these "top five" BHCs have lower volatility of accounting earnings and market returns than otherwise similar BHCs. These firms also appear to hold less risky loan portfolios and to engage in more conservative loan loss reserving practices. While their risk is lower, top five BHCs do not experience lower accounting returns or slower asset growth. Given that these firms are subject to similar rules, our results support the idea that supervision has a distinct role as a complement to regulation.
Keywords: G21; G28; 330; bank supervision; bank regulation; bank performance